On topological dimension - Azram, Mohammad (2009)
In this article ve will establish some basic but pivotal results regard.ing dimension of spaces with relative topologies. Most af the results are known to the readers but we have established their generalizaion through a simple vaiational approach. In the creative process, focus has been on well deJined simple concepts as an expeditious means of invotving mathematics loving students in research. We have esablished that any subset A C. 4 with dense A' C.- tt is of T4imension llsing inducrive approach, we have proved that dimension is in faa a npological invariant.